2021
DOI: 10.3390/ijerph18063213
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and Situational Variables Associated with Objective Knowledge on Water-Related Issues in a Northern Spanish City

Abstract: This study brings together the level of objective knowledge on water-related issues and other variables of psychological and situational nature. A random sample of 459 participants was employed, selected proportionally based on sex and age. In this sample, knowledge on the water-related issues tended to be low, particularly related to the direct source of water in the household, the type of services involved in the management, and consumption itself. In order to understand both the relationship with knowledge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…In addition, further research is needed to understand the moderation effect that positive and negative emotions cause in cognitive determinants of water-conservation behavior [69]. Past research states that including emotion in cognitive models enhances their model explanatory capacity regarding pro-environmental behavior [70]. Finally, concerning habits, our findings show that most research predominantly focuses on the link between past behavior and water consumption.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…In addition, further research is needed to understand the moderation effect that positive and negative emotions cause in cognitive determinants of water-conservation behavior [69]. Past research states that including emotion in cognitive models enhances their model explanatory capacity regarding pro-environmental behavior [70]. Finally, concerning habits, our findings show that most research predominantly focuses on the link between past behavior and water consumption.…”
Section: Discussionmentioning
confidence: 83%
“…The predominant method of measuring the dependent variable in the analyzed studies is self-reported measures (57%) (e.g., [68,69]), followed by behavioral intention to conserve or save water (27%) (e.g., [70,71]). To a lesser degree, actual water consumption has been used as a metric, encompassing variations such as "per-capita consumption" or "consumption per household" (7%).…”
Section: Theoretical and Conceptual Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…In Spain few studies reported profiles of users of water and watershed resources. In these studies, the majority of users are studying or have studied at the University: from more than 50% of users of Mar Menor watershed (Mediterranean basin; Velasco et al, 2018) and Valencian beaches (Cabezas-Rabadán et al, 2019), up to 80.8% of water users participating in a study in NW Spain (Andrade et al, 2021). Thus current university students like those included in our study, although not fully representative of all the users of water resources, would be-at least in the futurethe majority of water users in Spain.…”
Section: Discussionmentioning
confidence: 99%